PKM Kelompok Usaha Rumah Potong Ayam : Optimalisasi Produk dan Proses Produksi Berbasis Pemanfaatan Teknologi Tepat Guna di Desa Bulusan Kecamatan Kalipuro Kabupaten Banyuwangi - Lestari, Sutami Dwi; Qiram, Ikhwanul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
UMKM chicken slaughterhouse continues to grow along with the busyness of the community and the dynamics of social life. Chicken meat is one of the food ingredients that gives a very large contribution to the needs of animal protein which is quite high for humans. The Community Partnership Program (PKM) aims to increase productivity and knowledge of the Chicken Slaughtering Micro Business Group in Bulusan Village, Kalipuro District, Banyuwangi. PKM activities are carried out by producing production equipment such as energy-saving chicken feathers and energy storage media with sufficient capacity. This activity has an impact on increasing the productivity of businesses that are developed. In addition there was an increase in business turnover, operational knowledge of the tool so that the operational life of the tool is longer.